Psychology for teaching - O'Brien, Margaret (Wadsworth/Thomson Learning, 2000)
This ninth edition text incorporates additional material on the following topics: reflective teaching; holistic teaching; gender stereotyping; Thorndike; long term memory; giftedness; ADHD; performance-based assessment; and technology